The value of a law degree – part 2: a perspective from UK providers. Issue 2 (3rd April 2021) - Nicholson, Alex
ABSTRACT: For decades, law has been perceived as one of the most worthwhile degree programmes for students to undertake. In more recent years, contemporary rhetoric has begun to question the "value" of higher education in the modern world, and forthcoming regulatory changes in England and Wales will significantly dilute the concept of a "qualifying law degree", which in all likelihood has historically played a role in attracting large numbers of students to such programmes. In Part 1, theory from the marketing discipline was used to quantify holistically the true "value" of a law degree, with the aim of challenging the overly economic lens through which higher education is increasingly viewed, and constructing a theoretical model designed to help education providers identify, develop and articulate the value of their courses. This follow-up, empirical study builds on that earlier work by exploring the nature and extent of the "value" that is currently articulated by over 50 UK legal education providers on their online prospectus pages. The findings of this study are then used to propose a theory of "value" within the legal education sector, which can be used to identify opportunities for innovation and value creation.